2007
DOI: 10.1080/08916930701352357
|View full text |Cite
|
Sign up to set email alerts
|

Multiple specificities of autoantibodies against hnRNP A/B proteins in systemic rheumatic diseases and hnRNP L as an associated novel autoantigen

Abstract: Spliceosomal small nuclear ribonucleoproteins (U-snRNPs) are frequent and specific targets of autoantibodies in systemic rheumatic diseases. The abundant, functionally related heterogeneous nuclear ribonucleoprotein complexes (hnRNPs) have later defined as a new target of autoantibodies, of which their immunochemical/immunogenic and pathogenic properties are still under investigation. Among hnRNP proteins, those belonging to the A/B type are considered as the major autoantigens targeted by antibodies in sera o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 38 publications
0
25
0
1
Order By: Relevance
“…HnRNP-I is an autoantigen in SSc [213]. Anti-HnRNP-L autoAbs are found in association with hnRNP-A/B autoAbs [214]. AutoAbs to hnRNP-A1/A2/B1 were detected in the cerebrospinal fluid (but not in the sera) of 91% of patients with MS [215], and hnRNP-A1 Abs are found in cerebrospinal fluid and in sera of patients with HAM/TSP [216] (Table 9).…”
Section: Autoantibodiesmentioning
confidence: 96%
“…HnRNP-I is an autoantigen in SSc [213]. Anti-HnRNP-L autoAbs are found in association with hnRNP-A/B autoAbs [214]. AutoAbs to hnRNP-A1/A2/B1 were detected in the cerebrospinal fluid (but not in the sera) of 91% of patients with MS [215], and hnRNP-A1 Abs are found in cerebrospinal fluid and in sera of patients with HAM/TSP [216] (Table 9).…”
Section: Autoantibodiesmentioning
confidence: 96%
“…Subsequent identification and genecloning analysis showed that certain protein spots were in fact different isoforms generated from the same gene [39] with a total of 19 hnRNP genes identified. These proteins mainly function in the processing of precursor mRNA, but are also involved in telomeric DNA synthesis and apoptotic processes [40,41]. Through such functions, this family of proteins could potentially regulate tumorigenesis.…”
Section: Comparative Serum Analysis For Cts mentioning
confidence: 99%
“…Antibodies to hnRNP C1/C2 have been reported, but it is not known whether they are related to a specific disease (34 ). Recently, hnRNP L was identified as a novel autoantigen associated with anti-hnRNP A/B antibodies (29 ). hnRNP D (AUF1) was described as an autoantibody target in patients with systemic rheumatic diseases (mainly SLE and RA) (35 ).…”
Section: Discussionmentioning
confidence: 99%
“…They mainly play a role in processing of precursor mRNA, but are also involved in telomeric DNA synthesis and cellular apoptotic processes (27)(28)(29). hnRNPs are composed of at least 1 RNA recognition motif, also termed the RNA-binding domain.…”
Section: Discussionmentioning
confidence: 99%